1998
DOI: 10.1577/1548-8659(1998)127<0019:antetg>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Adding Nutrients to Enhance the Growth of Endangered Sockeye Salmon: Trophic Transfer in an Oligotrophic Lake

Abstract: Snake River sockeye salmon Oncorhynchus nerka listed under U.S. law as endangered in 1991 in response to a decline in anadromous adult numbers, spend their first 1–2 years in Redfish Lake, Idaho, before migrating to the sea. To determine how nutrient enhancement might influence phytoplankton, zooplankton, and fish production, we performed fertilization experiments in large enclosures in this oligotrophic lake using juvenile kokanee (lacustrine O. nerka) as analogues for endangered sockeye salmon. Fertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 46 publications
5
28
0
Order By: Relevance
“…This was evidenced both by the significant increase in periphyton Chl a concentrations in enriched sites over the relatively short duration of the experiment, as well as the rapid increase in ␦ 15 N signatures of periphyton following the initial addition of the tracer. Together, these responses indicate that periphyton can rapidly assimilate nutrients added to the water column in Lake McKenzie's littoral zone, and these findings support the assumption that primary producers (especially algae) in oligotrophic systems rapidly assimilate added nutrients (Budy et al 1998).…”
Section: Algal Response To Nutrient Andsupporting
confidence: 66%
See 1 more Smart Citation
“…This was evidenced both by the significant increase in periphyton Chl a concentrations in enriched sites over the relatively short duration of the experiment, as well as the rapid increase in ␦ 15 N signatures of periphyton following the initial addition of the tracer. Together, these responses indicate that periphyton can rapidly assimilate nutrients added to the water column in Lake McKenzie's littoral zone, and these findings support the assumption that primary producers (especially algae) in oligotrophic systems rapidly assimilate added nutrients (Budy et al 1998).…”
Section: Algal Response To Nutrient Andsupporting
confidence: 66%
“…However, results from algal bioassays are often difficult to extrapolate, and it is impossible to predict the long-term consequences of nutrient additions without an understanding of trophic transfer of nutrients from producers to higher order consumers (Mazumder and Lean 1994;Budy et al 1998).…”
mentioning
confidence: 99%
“…Wurtsbaugh, unpublished observation) where they may have been missed by our sampling procedure. In a similar limnocorral experiment done in a nearby oligotrophic lake, Budy et al (1997) demonstrated that epilimnetic nutrient enrichment increased both zooplankton and fish production. Because of conflicting evidence over the importance of algae in deep layers for zooplankton (cf.…”
Section: Figmentioning
confidence: 84%
“…The limnocorral experiment indicates that metalimnetic nutrient fertilizations may provide advantages over epilimnetic additions in programs designed to promote fish production (i.e., sockeye salmon; Budy et al 1997) especially when aesthetic impacts are important. The two strategies provided similar enhancement of primary production, but metalimnetic fertilization resulted in less periphyton and filamentous cyanobacteria growth, deeper Secchi depths, and greater phytoplankton biomass (as chlorophyll) than did the epilimnetic fertilization.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation